108 THE USE OF MARGINAL DONOR HEARTS IN HEART TRANSPLANT PATIENTS. (1st January 2005) - Alison-Mayne, S.; Patel, J. K.; Kobashigawa, J. A.; Laks, H.; Hamilton, M.
Abstract : Background: Use of marginal donor hearts in select patients (usually older recipients ≥65 years of age) waiting for heart transplant was implemented in 1992 at our institution to meet a growing shortage of donor organs. In this manner, we are able to match excluded potential recipients with donor hearts that would otherwise be unused. The long-term follow-up of these patients is being assessed to validate safety and efficacy of this policy. Methods: The criteria for marginal donor heart recipient list was age: 65 years old before 1998 and 70 years old after that. The marginal donor group consisted of 84 patients and the control group consisted of 763 patients transplanted from the regular list. Hearts were first offered to regular list patients and given to an marginal donor list patient for reasons of donor coronary artery disease, reused transplanted heart, high-risk behavior of donor, hepatitis seropositivity, decreased left ventricular ejection fraction, high inotropic requirement, left ventricular hypertrophy, donor age older than 55 years plus another risk factor, and small donor with no other matches. Results: Survival for marginal donor list patients was less than the regular list recipients at 5 years (59.5% vs. 76.0%, p≤0.003). Causes of death that were greater in the marginal donor group included malignancy (15.6% vs. 5.8%), multi-system organ failure (15.4% vs. 11.1%), and cerebrovascular disease (6.2% vs. 4.7%). Other causes of death among marginal donor and control groups included cardiovascular (3.1% vs. 12.1%), rejection 21.8% vs. 21.6%), and other (15.6% vs. 11.1%). Conclusion: Marginal donor list heart transplant patients compared to regular list patients have a lower 5-year survival. However, given the inherent increased mortality associated with the natural aging process, such as malignancy and cerebral vascular disease, post transplant survival in the marginal donor list group appears acceptable.